Unveiling the Journey Beyond: Understanding the Factors Influencing Pilgrimage Tourists' Revisiting Intention to Mecca - Neelam Bano,; Ahmad, Humaira; Hassan, Afsheen; Shaukat, Muhammad Awais; Dilshad, Sajida (Journal of Al-Tamaddun, 2024)
This qualitative study explores the multifaceted variables that influence pilgrimage tourists’ intention to return to Mecca, the holiest site in Islam, using the Stimulus-Organism-Response (S-O-R) theory. Every year, millions of Muslim pilgrims from around the globe converge on Mecca. Determining the factors influencing their intention to revisit is imperative for enhancing the overall pilgrimage experience and effective destination management. This study delves into the critical elements of the S-O-R model through in-depth interviews and thematic analysis to understand how pilgrimage tourists’ perceptions of Mecca as a destination (Stimulus), individual characteristics and experiences (Organism), and responses to the pilgrimage experience (Response) interact to shape their intention to revisit the sacred site. The results can help pilgrimage organizers, religious authorities, and tourism partners create meaningful and gratifying pilgrimage experiences while building long-term pilgrim loyalty to Mecca.